Comic Agonism in the 2016 Campaign: A Study of Iowa Caucus Rallies. (June 2019) - Warner, Benjamin R.; Galarza, Rocío; Coker, Calvin R.; Tschirhart, Philip; Hoeun, Sopheak; Jennings, Freddie J.; McKinney, Mitchell S.
In this study, we assess the extent to which attending a candidate rally was associated with distrust of democratic institutions, epistemic rigidity, attribution of malevolent intentions to the political outgroup, and acceptance of political violence. Surveys ( N = 251) were distributed at rallies the night before and day of the 2016 Iowa Caucuses. Results suggest that attendees of rallies for Bernie Sanders or Donald Trump were more likely to distrust democracy relative to attendees of a Hillary Clinton or Ted Cruz rally. Findings also suggest that mistrust of democracy was associated with greater attribution of malevolence and acceptance of political violence. Attending a Sanders or Trump rally was indirectly associated with attribution of malevolence and acceptance of political violence through democratic mistrust.